Retinal findings in carriers of monoallelic ABCC6 mutations. Issue 8 (28th March 2019) - Gliem, Martin; Wieg, Isabel; Birtel, Johannes; Müller, Philipp L; Faust, Isabel; Hendig, Doris; Holz, Frank G; Finger, Robert P; Charbel Issa, Peter
Abstract : Aim: Biallelic ABCC6 mutations cause pseudoxanthoma elasticum, a systemic disease characterised by calcification of elastic tissue and a specific retinal phenotype. In this study, we investigated if monoallelic ABCC6 mutations are also associated with retinal alterations. Methods: In this prospective, cross-sectional, monocentre case–control study, carriers of monoallelic ABCC6 mutations were investigated and compared with age-matched controls. The retinal phenotype was characterised using fundus photography, fundus autofluorescence, confocal near-infrared reflectance imaging, spectral domain optical coherence tomography and in selected cases late-phase indocyanine green angiography. Results: Thirty-eight subjects carrying monoallelic ABCC6 mutations (mean age 70.2 years, range 50–90, 26 female) were examined and compared with 77 age-matched controls (mean age 69.9 years, range 50–93, 43 female). Retinal alterations were more frequently found in carriers of monoallelic ABCC6 mutations compared with controls (50% vs 33.8%, p=0.107) with increasing prevalence at older age. Typical findings were peripapillary atrophy (37% vs 23%, p=0.184), pattern dystrophy-like changes (24% vs 12%, p=0.109), reticular pseudodrusen (21% vs 5%, p=0.019), small angioid streaks (8% vs 1%, p=0.105), choroidal neovascularisations and atrophic lesions (both 8% vs 0%, p=0.034). Late-phase indocyanine green angiography showed a reduced cyanescence centred to the posterior pole in 11 of 14 examined subjects with monoallelic ABCC6 mutations. Conclusion: The findings of this study indicate a possible ocular ABCC6 haploinsufficiency phenotype. Due to its late-onset and phenotypic similarities, misinterpretation as age-related macular degeneration is possible.